2020
DOI: 10.3390/su12051978
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility Dynamics and Regional Cross-Border Cooperation (CBC) Perspectives in the Portuguese—Spanish Borderland

Abstract: Accessibility plays a major role in achieving sustainable transport, and therefore urban and regional sustainability. The urban public transport system promotes mobility and realizes a large part of urban movements. Moreover, improving accessibility in order to promote sustainable transport requires the application of new concepts and indicators as a powerful tool in the process of creating a balanced urban transport system. In this regard, one of the main goals of this research is to present an overview of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 44 publications
(85 reference statements)
2
30
0
2
Order By: Relevance
“…Concerning the distance between cities, we have Oradea and Debrecen with the maximum distance possible of the pre-selection criteria (60km), the border cities of Frankfurt Oder and Slubice, and Cieszyn and Cesky Tesin with a distance around 1Km separating their urban centers. Nevertheless, as other similar studies have already shown, the distance has no much significance in the success of the CBC [27,28,29]. In this regard, we have the example of the border cities of La Línea de la Concepción (Spain) and Gibraltar (Gibraltar-UK), where the CBC is seen as a failure [10].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Concerning the distance between cities, we have Oradea and Debrecen with the maximum distance possible of the pre-selection criteria (60km), the border cities of Frankfurt Oder and Slubice, and Cieszyn and Cesky Tesin with a distance around 1Km separating their urban centers. Nevertheless, as other similar studies have already shown, the distance has no much significance in the success of the CBC [27,28,29]. In this regard, we have the example of the border cities of La Línea de la Concepción (Spain) and Gibraltar (Gibraltar-UK), where the CBC is seen as a failure [10].…”
Section: Discussionmentioning
confidence: 87%
“…Contextually, sentence d (Through the implementation of the CBC strategy, the job opportunities for both cities have increased), the answers showed an exact position of unclearnessonce the highest percentage was found in the agreement point 3 (with 38.8); even though, this affirmation also shows a slight agreement tendency. However, if we consider that the decision-makers and CBC representatives promise and announce better life quality standards, and many job opportunities for the local populations with the implementation of such border strategies -i.e., a recurrent situation in many of the Iberian Eurocities projects [28]; therefore, it was expected that those border populations select a higher level of agreement with this affirmation; which is are unfavorable findings for the government officials associated with this typology of activities. Indeed, past investigations confirm these discoveries and perspectives -i.e., [18,19,23,32,33,34,35,36,37,38,39] are just some examples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administrative boundaries had critical territorial implications, such as political, socioeconomic, regional or military implications, among many others [2,3,6]. With the implementation of these supportive EU policies, the borderland situation has undoubtedly improved in some structural ways, e.g., bridges, roads, and other infrastructures [7][8][9]. However, they have not been as effective in banishing the severe depopulation problems and economic decay that affect most of the Iberian border territories [2,3,10].…”
Section: The Starting Point: Deactivation Of the Portuguese-spanish Bmentioning
confidence: 99%
“…Regarding the Eurocities, there are also several relevant research works-i.e., in the Eurocities of Chaves-Verín [20,21,32]; Elvas-Badajoz [3,8,21,23], Tui-Valença [20], Bayona-Donostia [20,21], Douro-Duero [21], Cerdanya [20], and in the Lower Guadiana Region [20][21][22][23]. Moreover, studies were also conducted analyzing the whole of the Iberian Border [20][21][22][23][24]33].…”
Section: The Starting Point: Deactivation Of the Portuguese-spanish Bmentioning
confidence: 99%